1997
DOI: 10.1016/s0896-6273(00)80374-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Cocaine on Human Brain Activity and Emotion

Abstract: We investigated brain circuitry mediating cocaine-induced euphoria and craving using functional MRI (fMRI). During double-blind cocaine (0.6 mg/kg) and saline infusions in cocaine-dependent subjects, the entire brain was imaged for 5 min before and 13 min after infusion while subjects rated scales for rush, high, low, and craving. Cocaine induced focal signal increases in nucleus accumbens/subcallosal cortex (NAc/SCC), caudate, putamen, basal forebrain, thalamus, insula, hippocampus, parahippocampal gyrus, cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
778
4
19

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,152 publications
(852 citation statements)
references
References 93 publications
51
778
4
19
Order By: Relevance
“…Specifically, amphetamine weakened the suppressive effect of stress on the functional activity of cells in the CeA and MeA (see Figure 6). Interestingly, administration of cocaine in cocaine-dependent individuals reduces the functional activity of amygdaloid neurons, and this inhibition has been suggested to correlate with cocaine craving (Breiter et al, 1997). Electrophysiological studies indicate that infralimbic projection neurons synapse directly onto GABAergic intercalated cells in the CeA (Sesack et al, 1989;Royer et al, 1999;Quirk et al, 2003), which may be the source of amphetamine-induced decreases in functional activation in the CeA as observed herein.…”
Section: Discussionsupporting
confidence: 53%
“…Specifically, amphetamine weakened the suppressive effect of stress on the functional activity of cells in the CeA and MeA (see Figure 6). Interestingly, administration of cocaine in cocaine-dependent individuals reduces the functional activity of amygdaloid neurons, and this inhibition has been suggested to correlate with cocaine craving (Breiter et al, 1997). Electrophysiological studies indicate that infralimbic projection neurons synapse directly onto GABAergic intercalated cells in the CeA (Sesack et al, 1989;Royer et al, 1999;Quirk et al, 2003), which may be the source of amphetamine-induced decreases in functional activation in the CeA as observed herein.…”
Section: Discussionsupporting
confidence: 53%
“…One way to use fMRI to measure the effects of amphetamine on the baseline levels of neural activity, independent of task, might be to administer the drug intravenously. Indeed, it has been reported that intravenous infusions of cocaine, another psychostimulant, induced regionally specific fMRI activation (Breiter et al 1997) that was consistent with known neuroanatomical pathways and anatomical measurements of stimulant effects (Vollenweider et al 1998).…”
Section: Discussionmentioning
confidence: 61%
“…Several animal studies have suggested the "extended amygdala" as a neural substrate for the behavioral effects of self-administered cocaine (Robledo and Koob 1993;Caine and Koob 1994;Hurd et al 1997;McGregor and Roberts 1993;Robbins et al 1989;Robledo et al 1996). In humans, recent evidence from brain-imaging studies suggest a role for dopamine-rich brain regions, including the nucleus accumbens and amygdala, in cocaine craving (Grant et al 1996;Breiter et al 1997;Childress et al 1999). Along this line, considering the particular conditions of this work, it is tempting to speculate that, in addition to previously documented inhibition of mesocorticolimbic activity (Rossetti et al 1992;Kuhar and Pilotte 1996), a decrease in proenkephalin gene expression in the Ce may represent a possible mechanism mediating in cocaine withdrawal states.…”
Section: Discussionmentioning
confidence: 99%